دور السنن الإلهية في وعي الإنسان وتكامله الفكري - عبد الأمير حاتم عامر (Al-Adab Journal, 2018)
The holy Quran is considered the first book in history that indicates to the human society that there is rules and laws role the human movement who is apart of the society, and has a great relationship with his fate (happiness or misery). So that he should recognize and understand them, in order to be an active man and to control this laws otherwise they will control him unconsciously . This study is of three subjects of research : The first subject of research: the philosophy of divine laws. The Second subject of research Man and his role in the process of change. The third subject of research: Characteristics of the divine laws and their shapes.